PENGARUH MODAL INVESTASI MINIMAL DI BNI SEKURITAS, RETURN DAN PERSEPSI TERHADAP RISIKO PADA MINAT INVESTASI MAHASISWA, DENGAN PENGHASILAN SEBAGAI VARIABEL MODERASI (STUDI KASUS PADA MAHASISWA MAGISTER DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS UDAYANA) - Tandio, Daniel Raditya; Budiartha, I Ketut; Sadha Suardikha, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03. NO.07.TAHUN 2014, 2014)
Investment is no longer considered as something people wanted to get, but more like something people need. Preferences of return, risk and any investment programs are a part of factors that analyzed before making an investment. This research aims to test an effect of existence of minimum investment fund, return and perception of risk to interest of investment, with wage used as moderate variable. The analysis technique in this research is Moderated Regression Analysis (MRA). MRA was used because there is a need to test wage as the moderate variable. Students of Magister of Accounting, Magister of Management and Magister of Economy Sciences Department were being a population. The sampling method was Purposive sampling, with some criterias developed before. Questionnaire was used to collect data from participants. As much as 252 participants were participate. Based on MRA analysis, minimum investment fund does not affect interest of investment variable. Perception of risk and return are affecting interest of investment. Wage could not be a moderate variable. Key words: investment, return, risk, minimum investment fund, interest of investment, BNI Sekuritas .
Keywords: investment, return, risk, minimum investment fund, interest of investment, BNI Sekuritas